SMART-ER: a Situation Model of Anticipated Response consequences in Tactical decisions in skill acquisition — Extended and Revised - Raab, Markus (Frontiers in Psychology, 2015)
SMART (Situation Model of Anticipated Response consequences in tactical decisions) describes the interaction of top-down and bottom-up processes in skill acquisition and thus the dynamic interaction of sensory and motor capacities in embodied cognition. The empirically validated, extended, and revised SMART-ER can now predict when specific dynamic interactions of top-down and bottom-up processes have a beneficial or detrimental effect on performance and learning depending on situational constraints. The model is empirically supported and proposes learning strategies for when situation complexity varies or time pressure is present. Experiments from expertise research in sports illustrate that neither bottom-up nor top-down processes are bad or good per se but their effects depend on personal and situational characteristics.